Self-organizing expert communities in educational projects - Gennadiy P. Vinogradov; Vladimir N. Kuznetsov (Открытое образование (Москва))
Purpose of the study. The purpose of the study is the problem of forming a knowledge model of a specialist with higher education that is a part of an educational project. Its relevance is related to the need for an adequate response to strengthening the scientific and technological progress dynamics and the transition to the information interactions economy in the current conditions of the higher education system.Materials and methods. The information base of the research includes the laws on education of the Russian Federation, educational standards of higher professional education, scientists’ publications on the issues under investigation. The study used the following methods: system analysis, active systems theory, reflexive control theory, and modeling.Results. The research analyzes the consequences of Russia’s entry into the Bologna Convention on education. It shows that this event caused the problem of efficiency and quality of training specialists, as well as the problem of integrating higher education institutions into a new social and economic system related to their adaptation to market relations. According to the principle of institutional autonomy, solution of these problems is the responsibility of universities. The paper shows that the way to solve these problems is to transfer universities to a design and technological type of administration. The most promising form of education project management is the model of information interaction within the framework of active self-developing network expert environments. The elementary part of such an environment is an expert professional, who owns modern telecommunication technologies and Internet means. Integration in the natural intelligence network structure forms a collective strategic subject, which is a tool of a knowledge and action synergy in the interaction process. The paper describes the developed structure of the active self-developing network expert environment and two principles of its functioning as an active multi-agent system when forming a specialist knowledge model. It is proposed to consider the construction of specialist’s knowledge model in the context of corporate knowledge management strategies in organizations to increase competitiveness, as the established support systems for organization knowledge lifecycle and specialist’s integral knowledge model are used to integrate strategic corporate tasks with strategic tasks of developing employees’ corporate knowledge. They consider a specialist as an element of a company production system. His purpose is to give a product specified quantitative and qualitative parameters that ensure its competitive advantages. To carry out production activities, a specialist uses a complex of abilities, knowledge and skills that should be considered as models of his production and technological activities. At each moment, this complex should be considered as a subjective model of its production and technological activity. This creates a basis for a university self-development process by involving advanced consumers using network technologies in the innovative process of improving educational services, receiving ideas or content by referring to their creative abilities in exchange for a reward that corresponds to a contribution. The paper proposes a system that provides a direction for finding solutions and ideas, as well as filtering, summarizing information, determining its value and prospects. It is shown that the method of improving the quality of solutions on an educational project is the synthesis of crowdsourcing technologies, network expertise and the methodology of the active systems theory.Conclusions. The proposed approach allows considering the process of extracting new ideas and knowledge when forming a specialist’s knowledge model as an active system with heterogeneous agents with a counter way of sharing information and active influence of the center in the form of queries to obtain reflexive estimates. It also allows ensuring the interaction of universities and an organization in managing their intellectual capital.